Spatial distribution of mosquito vector in dengue outbreak areas in Kuala Lumpur and Selangor, Malaysia - Wan Najdah Wan Mohamad Ali,; Rohani Ahmad,; Zurainee Mohamed Nor,; Thuraiya Abdul Rahman,; Lim, Yvonne Ai-Lian (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
In Malaysia, the control of dengue is mainly through the identification and reduction of mosquito vector breeding sites. In this study, a larval survey was conducted from June 2017 until December 2018 to determine the spatial distribution of dengue vectors in the 132 dengue hotspots outbreak areas in Kuala Lumpur and Selangor. Molecular methods were performed in order to detect the presence of transovarial dengue virus in larvae collected, while the density of the breeding habitat and Aedes larval population were determine using spatial analysis. Map of Dengue virus (DENV) distribution were generated to illustrate the trend of dengue outbreak. This study showed that larval survey was an effective method to detect the presence of dengue virus transmission in immature Aedes aegypti and Aedes albopictus. This study also demonstrated that plastic container was the highest source of breeding habitat for Aedes mosquito, whereas blocked drain and tyre were the most favourable breeding habitats for Ae. aegypti and Ae. albopictus, respectively. Pearson’s correlation coefficient shows that mosquito density was not correlated with the DENV infection. In conclusion, current study shows that dengue transmission risk in Kuala Lumpur and Selangor remain high despite the outbreak response conducted by the health authority due to high density of Aedes population and the presence of DENV infection within the larvae population in the area. Therefore, new outbreak response methods such as public mandatory involvement in community-based control program to ensure success in management of resource reduction are necessary to ensure that the risk of dengue infection can be eliminated.